Population genetics and growth of the Rabbitfishes Siganus luridus and Siganus rivulatus: investigating factors structuring successful invasion of the Mediterranean Sea - Heyworth, Stephanie (2019)
Understanding the factors allowing for or, constraining the successful invasion of a new environment will be vital in predicting and monitoring the future success of invasive species. This is especially true in the context of the Mediterranean Sea where hundreds of species have invaded through the Suez Canal from the Red Sea over the last 140 years. Siganus luridus and Siganus rivulatus, two Lessepsian rabbitfish species, are among the most successful invaders established in the Mediterranean Sea to date, with abundant populations in the eastern, central and western Mediterranean. This project aimed to quantify the effectiveness of two factors for predicting invasion success; population genetic diversity and growth by examining populations of both species across 12 sites, from the eastern to the western Mediterranean basin. Samples from the Red Sea were also included in the phylogenetic analyses to allow for possible identification of founder effects within the introduced range. However, the small Red Sea sample size precluded their use from other analyses and made it impossible to investigate whether there had been an initial genetic bottleneck.